Controlled Synthesis of Hollow Hemispheric ZnO Shells/Cages on Graphite Fiber. (8th June 2011) - Liu, Xianbin; Du, Hejun; Zeng, Zhiyuan; Sun, Xiao Wei
Abstract : Hollow hemispheric ZnO shells/cages are synthesized on graphite fiber via simple thermal evaporation process. The cage-like ZnO structures exhibit micron or submicron size and hollow hemispheric shape with polycrystalline shell made of the ZnO nanocrystals. Controlled time-sequenced growth experiment is conducted to interpret the growth process, which indicates that the growth mechanism of the hollow hemispheric ZnO shells/cages involves formation of Zn particles firstly, followed by oxidation of the outer surface of Zn droplets and meantime sublimation of the core Zn.